Cina-Melayu di Bangka - Idi, Abdullah, 1965-; Huda, Nor, 1970- (Sleman, Yogyakarta : Tiara Wacana, 2009)
Assimilation of Chinese and Malay ethnic groups in Bangka Island
Bibliography : p. [275]-296
Keywords: Chinese -- Cultural asimilation -- Indonesia -- Bangka Island; Bangka Island (Indonesia) -- Ethnic relations